W optyce kompleksu emocjonalno-kognitywnego (inspiracje z wystawy „Chopinowi Duda-Gracz” - Tokarz, Bożena (Przestrzenie Teorii, 2024)
The article is devoted to the correspondence of arts (painting and music) in connection with the exhibition of various works by Jerzy Duda-Gracz at the Silesian Museum in Katowice. The author addresses the issue of methods for examining the community of various arts, regardless of the methodology assigned to each of them. He reaches for neuroaesthetics and broadly understood hapticity, in the literal and mediated sense, which explains the fact that painters see sounds, musicians see images, and poets see and hear words.